Educação e saúde ambiental em assentamentos rurais, Lagarto -SE - Santos, Alessandra Alcides de Sá (2015)
The present study addressed the environmental health education as a strategy for promoting health and the preservation of the natural environment, focusing on environmental sanitation concerns, aiming at establishing a greater social interaction and participation, in addition to portraying issues that arise from community necessities. The hereby stablished problematic suggests environmental health education as an interdisciplinary approach to ameliorating the human/environment relation, stating that its employment may favor a more appropriate awareness of a rural community self environmental health situation and its relation to the promotion of health and the preservation of the environment. This research theoretical premises were the inadequate environmental health situation found in the settlements, as well as the conceivable presence of association among social-environmental factors and the diseases referred by the settlement‟s population. Through this perspective, this enquiry points out as overall objective to bring to fruition a diagnosis of the environmental health situation in the municipality of Lagarto/SE, especially in two agrarian reform settlements assisted by Family Health Strategy, i.e., P.A. Camilo Torres and P.A. Karl Marx. The chosen methodology for this research was the mixed, qualitative quantitative approach, however, the quantitative data was limited to population aspects and to the records correlated to the overall health of the settlements. The environmental health situation diagnosis was accomplished with the GEO Health, which offered a participatory methodological emphasis based on integrated environmental and health indicators. The aim of the GEO Health Project is to develop an instrument capable of assessing the relationship between the health of the environment and human health, using of matrix of duly organized, integrated and analyzed basic indicators with a strong logical and conceptual framework. All 40 examined families inhabited houses constructed from brickwork, with access to electricity, septic fosses as small-scale sewage treatment system. 90% of their water supply is collected from rainwater harvest systems in cisterns, and also from artesian aquifers or even from rivers and water fountains near to settlements. Significant differences in environmental health conditions were found among the studied settlements, especially in regard to education, occupation, association between education and occupation, use of health services and diseases listed by the settlers related to the environment. Participative workshops employed during the research demonstrated the thematic axes, water quality and final destination to solid waste, in accordance to the prioritized problems from the settlers. Although the physical environmental present some positive aspects, settlers have limited access to the benefits and advantages that those structures could bring. Deficiency in maintenance and incorrect employment of these resources were among the main reasons for the inefficiency of the resources. Hopefully, therefore, this research and the actions consequentially employed may have contributed, in some way, to the enhancement of the environmental health conditions of the settlers, and that the methodology commissioned can be reproduced in other rural communities where similar problems happen, in compliance with their particular characteristics.